2013
DOI: 10.5935/abc.20130108
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Myocardial Infarction Protocol in Reducing Door-to-Ballon Time

Abstract: BackgroundAn adequate door-to-balloon time (<120 minutes) is the necessary condition for the efficacy of primary angioplasty in infarction to translate into effectiveness. ObjectiveTo describe the effectiveness of a quality of care protocol in reducing the door-to-balloon time. MethodsBetween May 2010 and August 2012, all individuals undergoing primary angioplasty in our hospital were analyzed. The door time was electronically recorded at the moment the patient took a number to be evaluated in the emergency ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
1
6
1
12
Order By: Relevance
“…However, with the advent of the digitalization of checklists by electronic-based systems, it was possible to overcome the deficiencies mentioned above but with considerable inconvenience due to reliance on fixed desktops when the patients had to be mobilized for various other diagnostic tests [17]. Real-time performance feedback to the healthcare team during STEMI activation is associated with a shorter door-toballoon time [18][19][20][21]. Besides, STEMI code activation can be done promptly, without having to progress through routine steps or being blocked by the physical boundaries of the hospital (e.g., the cardiology physician can respond and agree to activate the STEMI code even from outside the hospital).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the advent of the digitalization of checklists by electronic-based systems, it was possible to overcome the deficiencies mentioned above but with considerable inconvenience due to reliance on fixed desktops when the patients had to be mobilized for various other diagnostic tests [17]. Real-time performance feedback to the healthcare team during STEMI activation is associated with a shorter door-toballoon time [18][19][20][21]. Besides, STEMI code activation can be done promptly, without having to progress through routine steps or being blocked by the physical boundaries of the hospital (e.g., the cardiology physician can respond and agree to activate the STEMI code even from outside the hospital).…”
Section: Introductionmentioning
confidence: 99%
“…Of the full text publications, 357 did not meet basic study inclusion criteria. The CPW criteria were applied to 115 studies with 44 publications being included 911,3979 and 71 excluded. The most common reasons for exclusion were that studies were either not prospective (21.0%) or the intervention was not multidisciplinary (15.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Andrews et al 55 Zambia RCT Adult Sepsis Bekmezian et al 56 USA SBA-rp Both Asthma Callegro et al 57 Multinational SBA-rp Pediatric Febrile seizures Calver et al 58 Australia SBA-rp Adult Acute behavioral disturbance Chen et al 59 Taiwan SBA-pp Adult Stroke Chern et al 49 USA SBA-rp Pediatric CSF shunt malfunction Correia et al 60 Brazil SBA-pp Adult Myocardial infarction Crowe et al 61 USA SBA-rp Adult Sepsis Cruz et al 62 USA SBA-rp Pediatric Sepsis Dalcin et al 63 Brazil SBA-pp Both Asthma Decostered et al 64 Switzerland SBA-pp Adult Acute pain Dexheimer et al 65 USA RCT Pediatric Asthma Ender et al 66 USA SBA-pp Pediatric Sickle cell disease Fong et al 67 Australia SBA-rp Adult Head injury Geurts et al 52 Netherlands SBA-pp Pediatric Urinary tract infection Guse et al 51 USA SBA-rp Both Syncope Hoegerl et al 68 USA SBA-rp Adult Stoke Hyden et al 69 USA SBA-pp Adult Myocardial infarction Jones et al 70 USA SBA-pp Adult Sepsis Kim et al 71 Korea SBA-rp Both Pyelonephritis Lau et al 72 Hong Kong Prospective cohort Adult Stroke Li et al 73 Hong Kong Prospective cohort Adult Urinary retention Lougheed et al 11 Canada CBA Adult Asthma Mackey et al 74 Canada SBA-pp Both Asthma MacRedmond et al 75 Canada SBA-rp Adult Sepsis McCarthy et al 50 Ireland SBA-rp Adult Chronic obstructive pulmonary disease Mohd et al 76 Malaysia Prospective cohort Adult Sepsis Munoz et al 77 USA SBA-rp Adult Hyperglycemia Na et al 78 Multinational Prospective cohort Adult Sepsis Nguyen et al 13 USA Prospective cohort Adult Sepsis Norton et al 79 Canada SBA-pp Pediatric Asthma Paul et al 53 USA SBA-rp Pediatric Sepsis Plambech et al 80 Denmark SBA-rp Both Sepsis Ratanalert et al …”
Section: Country Study Design Study Population Clinical Entitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 57 Taiwan 2014 SBA-pp Adult Stroke Protocol Chern et al 23 USA 2010 SBA-rp Pediatric CSF shunt malfunction Clinical pathway/protocol a Correia et al 52 Brazil 2013 SBA-pp Adult Myocardial infarction Protocol Crowe et al 24 USA 2010 SBA-rp Adult Sepsis Protocol Cruz et al 25 USA 2011 SBA-rp Pediatric Sepsis Protocol Dalcin et al 26 Brazil 2007 SBA-pp Both Asthma Clinical pathway/protocol a Decostered et al 27 Switzerland 2007 SBA-pp Adult Acute pain Guideline Dexheimer et al 58 USA 2014 RCT Pediatric Asthma Protocol Ender et al 59 USA 2014 SBA-pp Pediatric Sickle cell disease Clinical pathway Fong et al 28 Australia 2008 SBA-rp Adult Head injury Guideline Geurts et al 60 Netherlands 2014 SBA-pp Pediatric Urinary tract infection Guideline Guse et al 61 USA 2014 SBA-rp Both Syncope Guideline Hoegerl et al 29 USA needs to be clarified, with specific emphasis placed on delineating the level of involvement of each discipline, and their decision-making responsibility. We found that only criterion 2 (the intervention was used to channel the translation of guidelines or evidence into local structures) resulted in quantifiable disagreement between reviewers.…”
Section: Protocolmentioning
confidence: 99%